(untitled) (Clinics, 2011)
OBJECTIVES: The aim of this study was to investigate the role of the interleukin-18 +105A/C and interleukin-10 -1082A/G germline polymorphisms in the development and outcome of differentiated thyroid carcinoma associated or not with concurrent thyroiditis. METHODS: We studied 346 patients with differentiated thyroid carcinomas, comprising 292 papillary carcinomas and 54 follicular carcinomas, who were followed up for 12-298 months (mean 76.10 ± 68.23 months) according to a standard protocol. We genotyped 200 patients and 144 control individuals for the interleukin-18 +105A/C polymorphism, and we genotyped 183 patients and 137 controls for the interleukin-10 -1082A/G polymorphism. RESULTS: Interleukin-18 polymorphisms were not associated with chronic lymphocytic thyroiditis or any clinical or pathological feature of tumor aggressiveness. However, there was an association between the presence of interleukin-10 variants and chronic lymphocytic thyroiditis. Chronic lymphocytic thyroiditis was present in 21.74% of differentiated thyroid carcinoma patients, most frequently affecting women previously diagnosed with Hashimoto's thyroiditis who had received a lower 131I cumulative dose and did not present lymph node metastases. CONCLUSIONS: We conclude that the inheritance of a G allele at the interleukin-10 -1082A/G polymorphism may favor a concurrent thyroid autoimmunity in differentiated thyroid carcinoma patients, and this autoimmunity may favor a better prognosis for these patients.